Institutional entrepreneurship and the forgotten origins of investment treaty arbitration - Taylor St. John (University of Oxford, Global Economic Governance Programme (GEG), 2014)
Advance consent clauses are the crux of modern bilateral investment treaties. By giving investors direct access to arbitration against states, they make the substantive promises of the treaties credible. They are responsible for the exponential increase in the number of investor-state arbitrations. Despite the importance of advance consent clauses, fundamental international political economy questions about their origins and development remain unanswered. This paper probes why advance consent clauses were created and how they disseminated. On the basis of new archival material, I argue institutional entrepreneurship played a vital and underappreciated role in the spread of advance consent. I systematically compare the explanatory power of institutional entrepreneurship with the explanatory power of state leadership, an approach informed by existing rational choice scholarship on these clauses, across three stages in the development and spread of advance consent. Although institutional entrepreneurship and state leadership both have explanatory power, institutional entrepreneurship is dominant: states inserted these advance consent clauses only after an IO drafted and disseminated them aggressively. The organization's top officials acted as institutional entrepreneurs - attempting to shape state preferences, acting as a knowledgebroker, and encouraging convergence - in order to ensure the survival of their organization. Studying the initial spread of advance consent clauses offers powerful insights into the development of the international investment regime and suggests scholars look beyond bilateral bargaining to understand its contours.
Keywords: 330; Internationales Investitionsrecht; Internationale Schiedsgerichtsbarkeit; Außenwirtschaftsrecht; Neue Institutionenökonomik